Magnetic Solid Phase Extraction of Au(III) using Fe3O4 Nanoparticles Prior to its Flame Atomic Absorption Spectrometric Determination - Khoshhesab, Zahra Monsef (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A simple solid phase extraction procedure has been proposed for determination of Au(III) based on separation and preconcentration using magnetite nanoparticles (MNPs) prior to its determination by flame atomic absorption spectrometry. The influences of experimental parameters including sample pH, sorbent mass, contact time, volume and type of eluent, and interference of some ions with extraction of Au(III) ions were investigated using batch procedure. The maximum adsorption capacity of the sorbent for Au(III) was found to be 45.0 mg g-1. The sorption of Au(III) ions was quantitative in the pH range of 4.0–5.0 and quantitative desorption was achieved using 10 mL of thiourea (0.5 mol L-1)/hydrochloric acid (1 mol L-1) solution. In the initial solution, the calibration curve was linear in the range of 8.8 - 666.0 μg L-1 with R2 = 0.9994 (n = 8), the detection limit (3Sb, n = 8) was 6.2 μg L-1, relative standard deviation (R.S.D) of 20 μg mL-1 of Au(III) was 3.9% (n = 8), and the preconcentration factor was 30. The proposed method has been applied to the determination of Au(III) in water and wastewater samples with good recoveries in the range of 95% –103%.